Teologi Keselamatan: Analisis Penyebab Kejatuhan dan Sifat Dosa dalam Ajaran John Wesley dan John Calvin - Octavianus, Jonathan; Sung Kun , Kim (Kaluteros Jurnal Teologi Dan Pendidikan Agama Kristen, 2024)
The theology of salvation is a central topic in Christian thought that addresses the origin of sin and how humanity can attain salvation. One of the interesting issues to explore is the cause of humanity's fall into sin and the nature of sin itself, as taught by two prominent theological figures, John Wesley and John Calvin. This article aims to analyze the views of these two figures regarding the causes of humanity's fall into sin and the nature of sin following the fall. The objective of this study is to examine the similarities and differences in the understanding of John Wesley and John Calvin concerning the theology of salvation, particularly regarding the causes and nature of sin. This research employs a comparative analysis method, wherein the author compares the major works of both theological figures and examines their views on the subject matter. The findings of the study reveal that both John Wesley and John Calvin agree that the cause of humanity's fall is the misuse of free will. However, they differ in their interpretation of the nature of sin that arises from the fall. Wesley emphasizes the impact of sin, which leads to pride and selfish desires, while Calvin views it in a broader context as humanity's inability to save itself. In conclusion, although there is agreement on the basic views, both offer distinct theological implications regarding sin after the fall.